A photographer's life 1990 - 2005 - Leibovitz, Annie 1949- (Random House, 2006)
A visual narrative offers more than three hundred images that document the photographer's relationship with her late companion Susan Sontag, the birth of her daughters, the death of her father, and famous actors and politicians.
Keywords: Leibovitz, Annie -- 1949- -- Exhibitions; Leibovitz, Annie -- 1949-; Geschichte 1990-2005; Portrait photography -- Exhibitions; Fotografie; Ausstellungskatalog; Bildband